2015
DOI: 10.1103/physrevc.91.054003
|View full text |Cite
|
Sign up to set email alerts
|

Three-body bremsstrahlung and the rotational character of theC12spectrum

Abstract: The electric quadrupole transitions between 0 + , 2 + , and 4 + states in 12 C are investigated in a 3α model. The three-body wave functions are obtained by means of the hyperspherical adiabatic expansion method, and the continuum is discretized by imposing a box boundary condition. Corresponding expressions for the continuum three-body (3α) bremsstrahlung and photon dissociation cross sections are derived and computed for two different α-α potentials. The available experimental energy dependence is reproduced… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 46 publications
(216 reference statements)
0
23
0
Order By: Relevance
“…The results are similar no matter what method is used to extract the transition strengths (B σ or B γ ), especially when taking into account the uncertainties inherent to each of the methods. Although not shown, it has also been observed that the results are, to a large extent, independent of the potential used [4]. An important result is that the 4 .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The results are similar no matter what method is used to extract the transition strengths (B σ or B γ ), especially when taking into account the uncertainties inherent to each of the methods. Although not shown, it has also been observed that the results are, to a large extent, independent of the potential used [4]. An important result is that the 4 .…”
Section: Discussionmentioning
confidence: 91%
“…It is important to note that the summation over i and j in the Eq. (3) is not unrestricted, but limited to the initial and final energy ranges of experimental interest [4].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is a well known fact that using only twobody potentials will usually lead to an underbound threebody structure, as shown for instance for 17 Ne and 12 C in Refs. [23,39], respectively. This problem is typically overtaken by addition of an effective three-body force, V 3b (ρ), to the adiabatic potential given in Eq.…”
Section: Figmentioning
confidence: 99%
“…This problem can be handled by two conceptually different methods [39,41], where the first is to specify the boundary conditions directly and solve the Schrödinger equation. The second method is to discretize the continuum in a large hyperradial box which in the present case is limited by hyperradii less than the box radius ρ max .…”
Section: A Excited Continuum Statesmentioning
confidence: 99%